Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.


Given the function that g(x) = 2x² − 5x + 1, find each of the following.
-
a) g(0)
b) g(-2)
c) g(4)
d) g(-x)
e) g(1 – t)


Sagot :

Step-by-step explanation:

g(x) = 2x² − 5x + 1

a) g(0)

g(0)=2[tex](0)^{2}[/tex]-5(0)+1

      =1

b) g(-2)

g(2)=2[tex](-2)^{2}[/tex]-5(-2)+1

    =8+10+1

    =19

c) g(4)

g(4)=2[tex](4)^{2}[/tex]-5(4)+1

   =32-20+1

   =11

d) g(-x)

g(x) = 2x² − 5x + 1

g(-x)=2[tex](-x)^{2}[/tex]-5(-x)+1

   =2[tex]x^{2}[/tex]+5x+1

e) g(1 – t)

g(x) = 2x² − 5x + 1

g(1-t)=2[tex](1-t)^{2}[/tex]-5(1-t)+1

     =2[tex]t^{2}[/tex]+t-2

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.